1983
DOI: 10.1073/pnas.80.23.7160
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of methionine residues in proteins of activated human neutrophils.

Abstract: A simple assay for the detection of 35S-labeled methionine sulfoxide residues in proteins is described. The assay, which is based on the ability of CNBr to react with methionine but not with methionine sulfoxide, requires the prelabeling of cellular proteins with [3S]methionine. The assay was used to study the extent of methionine oxidation in newly synthesized proteins of both activated and quiescent human neutrophils. In cells undergoing a phorbol 12-myristate 13-acetate-induced respiratory burst, about 66% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Generation of such high levels of oxidized Met in completed proteins by stimulated neutrophils is unique and has, so far, not been reported. Usually, Met residues are located within the hydrophobic interior of completed proteins where they seem to be more or less resistant to oxidation in contrast to Met residues in nascent polypeptide chains [6,12]. Quantitation of the Met(O) content in in- Table 1 Met ( portion of oxidized Met in the proteins released was found to be 28% (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generation of such high levels of oxidized Met in completed proteins by stimulated neutrophils is unique and has, so far, not been reported. Usually, Met residues are located within the hydrophobic interior of completed proteins where they seem to be more or less resistant to oxidation in contrast to Met residues in nascent polypeptide chains [6,12]. Quantitation of the Met(O) content in in- Table 1 Met ( portion of oxidized Met in the proteins released was found to be 28% (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In cells undergoing PMA-induced respiratory burst, 22% of all methionine residues in the total protein were oxidized to the sulfoxide. In contrast, about 66% of all methionine residues in proteins newly synthesized during stimulation were oxidized to the sulfoxide [6]. Newly synthesized, i.e.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Our suggestion that free radicals are responsible for methionine sulfoxide production from methionine is not completely new. Recent data published in [24] also suggest an oxidative role of oxygen free radicals generated by human neutrophils in the appearance of protein-bound methionine sulfoxide. Studies on the mechanism of the photo-oxidation of free amino acids showed unambiguously involvement of singlet oxygen ~O2 in this process [14].…”
Section: Discussionmentioning
confidence: 99%